2000
DOI: 10.1046/j.1471-4159.2000.0740295.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Neuritotrophic Cytokine S100β Precedes the Appearance of Neuritic β‐Amyloid Plaques in APPV717F Mice

Abstract: Homozygous APPV717F transgenic mice overexpress a human beta-amyloid precursor protein (betaAPP) minigene encoding a familial Alzheimer's disease mutation. These mice develop Alzheimer-type neuritic beta-amyloid plaques surrounded by astrocytes. S100beta is an astrocyte-derived cytokine that promotes neurite growth and promotes excessive expression of betaAPP. S100beta overexpression in Alzheimer's disease correlates with the proliferation of betaAPP-immunoreactive neurites in beta-amyloid plaques. We found ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 32 publications
(47 reference statements)
2
36
0
1
Order By: Relevance
“…96 The tissue levels of S100B mRNA and protein were elevated at each month from the second to eighth and from that time were correlated with Aβ load in these mice. 96 In addition, the expression of the IL-1β-converting enzyme is greatly increased in these mice, again before plaque formation, and was closely correlated with neuronal DNA damage and cell loss. This is consistent with the idea that increases in active IL-1β contribute to Aβ plaque formation and to neuronal degeneration in mouse models of AD and by analogy to AD.…”
Section: 95mentioning
confidence: 79%
“…96 The tissue levels of S100B mRNA and protein were elevated at each month from the second to eighth and from that time were correlated with Aβ load in these mice. 96 In addition, the expression of the IL-1β-converting enzyme is greatly increased in these mice, again before plaque formation, and was closely correlated with neuronal DNA damage and cell loss. This is consistent with the idea that increases in active IL-1β contribute to Aβ plaque formation and to neuronal degeneration in mouse models of AD and by analogy to AD.…”
Section: 95mentioning
confidence: 79%
“…The cytokine cycle leads to the release of large amounts of pro-inflammatory cytokines and toxic substances by activated microglia and astrocytes, such as oxygen radicals and nitric oxide, resulting in further enhancement of brain inflammation and bystander injury in AD (Griffin et al, 1998b;Akiyama et al, 2000). In fact, it has been shown that S100B production is up-regulated in patients with AD (Mrak and Griffin, 2001), and overexpression of S100B precedes the appearance of neuritic ␤-amyloid plaque pathology in a transgenic mouse model of AD (Sheng et al, 2000). Moreover, neuritic changes in ␤-amyloid plaques in Down's syndrome were shown to be closely associated with astrocytic overproduction of S100B (Griffin et al, 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pharmacological suppression of astrocytic S100B synthesis by arundic acid may have dual significance in slowing the progression of the disease process; in AD cerebral regions demarked by relatively low levels of S100B, arundic acid might inhibit neurite extension in response to cerebral amyloidosis, thereby decreasing neuroplastic burden. In AD brain regions with high levels of S100B, the agent may attenuate the damaging cytokine cycle, hence suppressing the autotoxic loop and reducing ␤-amyloid plaque formation (Mrak et al, 1996;Sheng et al, 2000;Mrak and Griffin, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100B has also been shown to enhance neuronal survival and stimulate neurite outgrowth and astrocyte proliferation at nanomolar concentrations (2,3,6,7,16,20,21,23,39,47) and to cause neuronal and astrocyte apoptosis and stimulate interleukin-6 secretion by neurons and nitric oxide release by astrocytes and microglia at micromolar concentrations (1, 18-20, 25, 27, 31). Therefore, S100B has been hypothesized to play roles in brain development and neuronal protection (2,3,6,7,16,20,21,23,39,47) and in the pathophysiology of neurodegenerative disorders (15,20,30,40,41), depending on the concentration attained in the extracellular space. Trophic effects of S100B on neurons have been shown to depend on activation of the transcription factor NF-B (3).…”
Section: S100b Is a Camentioning
confidence: 99%